LITERATURE RIVIEW : GAMBARAN TINGKAT KECEMASAN KELUARGA DALAM MERAWAT ANGGOTA KELUARGA PENDERITA SKIZOFRENIA - Tinah Tinah; Zubaida (Poltekkes Kemenkes Medan, 2022)
Schizophrenia is a persistent and serious brain disease that results in psychotic behavior, concrete thinking and difficulty processing information, interpersonal relationships, and problem solving. family is an open system, which means a change or disruption in one part of the entire system. This means that when one member of the family suffers from schizophrenia, the whole family feels the negative impact. Families generally experience feelings of sadness, anxiety, fear, worry and confusion in dealing with family members who experience schizophrenia.To find similarities, strengths and weaknesses of family anxiety levels in caring for family members with schizophrenia. based on the literature review study. From the literature review. In general, the level of family anxiety in caring for family members with schizophrenia is moderate.